Discipline-specific cognitive differences in esports: DOTA 2 and Counter-Strike 2 - Talan, A.S.; Demeshkin, I.; Myagkov, M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify discipline-specific cognitive differences between DOTA 2 and Counter-Strike 2 players using validated digital trainers. Methods and structure of the study. Thirty-seven males aged 18-25 years participated in the study: Counter-Strike 2 players: n=15 (age 20.8 ± 1.9 years), DOTA 2 players: n=12 (age 21.4 ± 2.3 years), non-players (control group): n=10 (age 21.7 ± 2.0 years). Inclusion criteria for esports athletes: active gaming activity for at least 400 hours in the selected discipline, participation in amateur or semi-professional tournaments. Average MMR rating in DOTA 2 was 6000, in Counter-Strike 2 — 2500. Exclusion criteria: presence of neurological diseases, uncorrected vision disorders. Results and conclusions. The results demonstrate statistically significant discipline-specific differences: DOTA 2 players outperform CS2 players in accuracy (d=-2.078), number of targets hit (d=-1.495), and have advantage in reaction time (d=1.059). Both esports groups significantly outperformed the control group in most cognitive measures. The study confirms the applicability of the discipline-specific approach in sports science and validates the use of digital trainers for objective assessment of cognitive abilities.